Pengaruh Konsentrasi Giberelin (GA3) Terhadap Nilai Nutrisi Calopogonium caeruleum - Asra, Revis; Ubaidillah, Ubaidillah (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2012)
This research was conductedÂ  to reveal the effect of the Gibberellins concentrationÂ  (GA3) on the content of crude protein (CP), acid detergent fiber (ADF) and neutral detergent fiber (NDF) of Calopogonium caeruleum. The design of experiment was the Completely Randomized Design (CRD) in factorial arrangement. The first factors were the concentrations of GA3 namely 0, 100, 200, 300, 400 and 500 ppm, for G0,G1, G2, G3, G4, and G5 respectively and the second factors were the soaking time at 6, 12 and 24 h, for T1, T2 and T3 respectively. Each treatment has three replications. The results showed that there were not significant (P< 0.05) effect of the concentration of GA3 on the content of CP, ADF and NDF of Calopogonium caeruleum.